Agenesis of the infra-hepatic segment of the inferior vena cava associated with recurrent deep venous thrombosis: Case report - Grillo, Vinicius Tadeu Ramos da Silva [UNESP]; Filho, Pedro Luciano Mellucci [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Bertanha, Matheus [UNESP]; Pimenta, Rafael Elias Fares [UNESP]; Sobreira, Marcone Lima [UNESP] (FapUNIFESP (SciELO), 2021)
Agenesis of the inferior vena cava (IVC) has been described in less than 1% of the population; a rare occurrence caused by embryonic abnormalities. Its correlation with deep vein thrombosis (DVT) is certainly underestimated, since this change is hard to detect using ultrasound. The aim of the article is to report the case of a 41-year-old female patient with pain and edema up to the top of the right thigh after plastic surgery. Bilateral venous duplex ultrasound revealed bilateral DVT involving iliac-femoral-popliteal and distal segments. Venous angiotomography was requested because the IVC was not visible on ultrasound, revealing thrombosis of the right lumbar plexus and iliofemoral segment bilaterally and agenesis of the infrahepatic segment of the inferior vena cava, with ectasia and compensatory tortuosity of paravertebral veins and the azygos-hemiazygos system, and bilateral pelvic varices. Systemic and oral anticoagulation were administered, with a satisfactory clinical response.
Agenesia de segmento infra-hepático de veia cava inferior associada a trombose venosa profunda de repetição: Relato de caso
Keywords: Cardiovascular abnormalities; Deep venous thrombosis; Inferior vena cava